Wideband end‐fire circularly polarised complementary source antenna for millimetre‐wave applications. Issue 15 (29th November 2021) - Wang, Jingxue; Wu, Fan; Jiang, Defu; Li, Yujian
Abstract: A millimetre‐wave end‐fire circularly polarised (CP) complementary source antenna is proposed. Circular polarisation is obtained by combining a quarter‐wave shorted patch and a planar electric dipole. A direct‐feeding method based on the use of substrate integrated coaxial line (SICL) is developed for wideband excitation of the antenna. The antenna element achieves a −10‐dB impedance bandwidth of more than 32.4% and a 3‐dB AR bandwidth of 30.1% with a stable gain around 5.5 dBic. To demonstrate higher antenna gain, a 1 × 4 CP antenna array fed by an SICL power divider is designed. Measurement of the fabricated prototype verifies that the CP antenna array achieves a gain up to 10.5 dBic. The competitive performances including wide bandwidth, stable gain, and simple planar configuration make the proposed CP antenna attractive for millimetre‐wave applications such as the fifth‐generation (5G) mobile communications and the next generation WiFi systems.